(untitled) (Fiep Bulletin - online, 2014)
Students arriving at Federal Institutes bring their experiences and they can contribute positively to their learning or not. The teacher who works with the discipline of human anatomy, realize in their daily practice that does not have as much progress in his teaching because despite the advanced technology, bones, muscles and tendons are still bones, muscles and tendons. Therefore, a doubt arose that sought to remedy this research: that knowledge in anatomy students arrive at Federal Institutes? Seeking to identify the knowledge of students in the 1st period of the Federal Fluminense Campus Cabo Frio RJ Course Natural Sciences, in relation to anatomical structures systemic and locomotor, using the method of questionnaire, where students have access to 18 questions about the gross anatomy of the human body and scored on a figure that was with some squares and the same would have to mark the box in an "X " corresponding to the correct question. The questions are related to the following structures: heart, spleen, thyroid, kidney, carpal bones, fibula, radio, clavicle, femur, rotator cuff, biceps, supinator, quadriceps, pectineus, tarsal bones, cremaster muscle, tibia and deltoid. For the 28 students of Natural Sciences, investigated gave the following result, concluded that in relation to the knowledge of students of the 1st course of Natural Sciences of the Federal Fluminense - Campus Cabo Frio, RJ, compared anatomical structures have the following percentage of correct answers: heart (100%), spleen (14%), thyroid (100%), kidney (100%); carpal bones (93%), the fibula (71%); radio (79%); clavicle (89%); femur (89%); rotator cuff (64%); biceps brachial (71%); supinator (96%); quadriceps (21%); pectineal (14%); tarsal bones (79%); cremaster muscle (43%), tibia (89%), deltoid (79%).